Teachers’ motivation in developing quality learning in rural schools in Indonesia - M. Dahlan R; Samsuri; Elih Malihatun; Buci Morisson; Asep Abdurrohman; Abdul Basyit; Madali (Frontiers in Education)
This study examines teachers’ interests influenced by school culture and organizational and civic behavior through life satisfaction in developing quality learning. The researcher conducted this study in the province of West Java, Indonesia. The subjects of this study are 193 elementary school teachers. Data collection techniques used school culture instruments, organizational, civic behavior, life satisfaction, teacher interests, and data analysis techniques using structural equations (SEM). This research shows that school culture and organizational and civic behavior through life satisfaction play an essential role in fostering teachers’ interest. Teachers’ interest results from the school’s cultural encouragement, organizational, civic behavior, and life satisfaction. This research implies that programs must develop teachers’ interests by optimizing school culture, managerial and civic behavior, and meeting life needs as influential factors. The results of this study show a positive and significant relationship between the variables studied. These findings can serve as a basis for institution owners and policymakers to assess the effects of teachers’ interests and develop strategies to improve the quality of learning.